Where ecosystems, people and health meet:: academic traditions and emerging fields for research and practice - Oestreicher, Jordan S.; Buse, Chris; Brisbois, Ben; Patrick, Rebecca; Jenkins, Aaron; Kingsley, Jonathan; Távora, Renata; Fatorelli, Leandra (Sustainability in Debate, 2018)
Human-driven environmental change has brought attention to the importance of ecosystems in sustaining human health and well-being. There are various schools of thought and fields of inquiry and action that seek to understand health in relation to linked social and ecological phenomena. We describe 18 such fields and outline common elements and incongruities among them. They converge around the application of systems thinking and crossing disciplinary boundaries, while differences are found in methodologies, research foci and problem framing. Although fields encourage sustainable and equitable pathways for health promotion, depoliticized and ahistorical approaches continue to be standard practice. Future research calls for a deeper commitment to examining ourselves as political actors, making space for conversations around power dynamics, and (re)centering participants in research methodologies.